(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1990)
Several detailed stratigraphical sections have been measured in the Middle Jurassic of the Zanskar region (Western Himalaya, Ladakh, India). Along six sections in the Laptal Beds and in the Ferruginous Oolite Formation, a rich brachiopod fauna, associated with a few ammonites, has been collected. Most of the brachiopod species are new for the Himalayan region, been so far typical of the Northern Tethys margin. A species, lvanoviella gaetanii sp. n., is erected on material from the Ferruginous Oolite Formation. The age of the lithostratigraphic units yielding fossils is discussed from both brachiopods and ammonites: though little discrepancies are present between the inferred age of brachiopods and ammonites, a Bathonian age for the Laptal Beds and a ?Bathonian, Early Callovian to Oxfordian age for the Ferruginous Oolite Formation is established.